COMPARISON OF THE FINANCIAL PERFORMANCE OF DIGITAL BANKS AND CONVENTIONAL BANKS USING THE CAMELS METHOD - Lius Dionosius; Randy Kuswanto (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to compare the financial performance of digital banks and conventional banks in Indonesia using the CAMELS method. A quantitative descriptive design with a pair-matching sample approach was employed. Ten banks (5 digital banks and 5 conventional banks) were selected based on asset equivalence in 2023. Secondary data from financial statements were analyzed using Mann-Whitney U and Wilcoxon statistical tests. The results reveal significant differences in financial performance between digital banks and conventional banks (p < 0.05). Conventional banks recorded higher averages in Capital Adequacy Ratio (CAR) and Return on Assets (ROA), reflecting better operational efficiency and financial stability. In contrast, digital banks exhibited higher operational costs (BOPO) and negative profitability, indicating challenges in managing operational efficiency. CAMELS scores demonstrated fluctuations in digital banks, whereas conventional banks showed greater stability over the 2020–2023 period. In-depth analysis suggests that digital banks face higher operational risks due to intensive technological transformation, despite their significant potential for long-term service efficiency. Meanwhile, conventional banks with established business models excel in risk management and operational stability. This research contributes to banking literature by highlighting the importance of risk management strategies and operational efficiency tailored to the unique characteristics of each bank type.